Advances in platinum-based and platinum-free oxygen reduction reaction catalysts for cathodes in direct methanol fuel cells - Qin, Chu; Tian, Shijun; Wang, Wenjie; Jiang, Zhong-Jie; Jiang, Zhongqing (Frontiers in Chemistry, 2022)
Direct methanol fuel cells (DMFCs) have been the focus of future research because of their simple structure, abundant fuel sources, high energy conversion efficiency and low cost. Among the components in DMFC, the activity and stability of the cathode catalyst is the key to the performance and lifetime of the DMFCs. Oxygen reduction reaction (ORR) is an important electrode reaction on DMFC cathode. It is known that Pt is widely used in the fabrication of ORR catalysts, but the limited earth storage of Pt and its high price limit the use of Pt-based commercial catalysts in DMFCs. To overcome these problems, advances have been made on new low Pt-based catalysts and Pt-free catalysts in recent years. In this article, the development of novel ORR catalysts and the carbon supports is reviewed and discussed.